Structure, Morphology, and Optical Properties of (Cal(1-3x)Eu(2x)) WO4 Microcrystals - Goncalves, R. F.; Godinho, M. J.; Marques, A. P. A.; Santos, M. R. C.; Rosa, I. L. V. [UNESP]; Longo, Elson; Li, M. Siu; Sa, J. L. S.; Cavalcante, L. S. (Korean Inst Metals Materials, 2015)
In this letter, we report the efficient, surfactant-free, microwave-hydrothermal method of synthesizing calcium europium tungstate [(Ca1-3XEu2X) WO4, x= 0, 0.05, 0.01, 0.02, and 0.04] microcrystals. The structure and morphology were investigated using X-ray diffraction (XRD), Fourier-transform Raman (FT-Raman) spectroscopy, and field emission scanning electron microscopy (FE-SEM). XRD patterns and FT-Raman spectra indicated that all (Ca1-3Eu2X)WO4 microcrystals has a scheelite-type tetragonal
Keywords: CaWO4; Microcrystals; Europium; Microwave; Raman; Photoluminescence